2004
DOI: 10.1637/7105
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Resistance Plasmid Transfer in Escherichia coli by Ionophores, Chlortetracycline, Bacitracin, and Ionophore/Antimicrobial Combinations

Abstract: Medicinal feed additives bacitracin, chlortetracycline (CTC), laidlomycin, lasalocid, and salinomycin inhibited the transfer of multiresistance-conferring plasmid pBR325 (Tet(r) Amp(r) Cp(r), 6.0 kb) into selected gram-negative strains with the use of an in vitro model. High concentrations of ampicillin-sensitive competence-pretreated Escherichia coli HB 101 cells were exposed to 10% (v/v) of 1:10 dimethyl sulfoxide/agent : water containing test mixtures for 0.5 hr prior to plasmid addition and transforming co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A Danish study found that 100% of organic broiler flocks, 49.2% of extensive indoor flocks, and 36.7% of conventional flocks were positive for Campylobacter (Heuer et al, 2001). Recent evidence suggests that several ionophores and antibiotics (including chlortetracycline and bacitracin) actually appear to inhibit transfer of genetic elements (specifically the multidrug-resistance plasmid pBR325) among bacteria (including several strains of E. coli and 1 strain of Salmonella typhimurium), possibly reducing the spread of acquired resistance (Mathers et al, 2004).…”
Section: Potential Consequences Of Antibiotic Bansmentioning
confidence: 99%
“…A Danish study found that 100% of organic broiler flocks, 49.2% of extensive indoor flocks, and 36.7% of conventional flocks were positive for Campylobacter (Heuer et al, 2001). Recent evidence suggests that several ionophores and antibiotics (including chlortetracycline and bacitracin) actually appear to inhibit transfer of genetic elements (specifically the multidrug-resistance plasmid pBR325) among bacteria (including several strains of E. coli and 1 strain of Salmonella typhimurium), possibly reducing the spread of acquired resistance (Mathers et al, 2004).…”
Section: Potential Consequences Of Antibiotic Bansmentioning
confidence: 99%
“…Antimicrobial agents currently approved for use in animals (bacitracin, chlortetracycline, and ionophores) have been shown to inhibit in vitro resistance plasmid transfer in E. coli. [50][51][52] These studies offer the possibility that new agents used in food animals might themselves contain intrinsic activity to minimize resistance transfer, such as proposed for human pathogens. 53 Novel screening technologies and targets intended for new antimicrobial agents for human therapeutics continue to emerge.…”
Section: Current Research Approaches To Fill the Antimicrobial Agent mentioning
confidence: 99%
“…However, the balance of the influences of antimicrobial compounds (in the broadest sense) on the horizontal transfer of AMR on farms is poorly understood, as it may include inhibition as well as promotion of gene transfer. Work on antimicrobials used as growth promoters, plus some (including chlortetracycline and tylosin) used for prophylaxis and therapy, showed considerable inhibition of plasmid transfer into E. coli at normal in‐feed concentrations (Mathers et al., ), while chlorhexidine and some quaternary ammonium compounds (QACs) (applied at or just below their minimum inhibitory concentrations [MICs]) also reduced plasmid transfer (Al‐Masaudi, Day, & Russell, ). Some antibacterial compounds, such as certain unsaturated fatty acids, have a specific antiplasmid‐transfer effect (Getino et al., ).…”
Section: Introductionmentioning
confidence: 99%